PENERAPAN QUIZIZZ PAPER MODE SEBAGAI MEDIA ASESMEN FORMATIF UNTUK MENINGKATKAN HASIL BELAJAR IPAS SISWA KELAS V MI MUHAMMADIYAH KALOSI - Sulida; Dian Firdiani; Fuad Danindra (STKIP Subang, 2026)
This study was motivated by the low learning outcomes of fifth-grade students in IPAS at MI Muhammadiyah Kalosi, with an average score of 60.67 and only 4 out of 18 students (22.22%) achieving the good and very good categories. This condition was caused by conventional assessment methods, lack of immediate feedback, and limited technology use in evaluation activities. This study aimed to describe the implementation of Quizizz Paper Mode as a formative assessment media and to examine the improvement of students' learning outcomes. This research employed Classroom Action Research (CAR) conducted in two cycles, consisting of planning, action, observation, and reflection stages. Subjects were 18 fifth-grade students. Data were collected through learning outcome tests, observation, and documentation. The results showed an improvement in learning outcomes: from 22.22% mastery with an average of 60.67 in the pre-action stage, to 55.56% with an average of 68.89 in Cycle I, and significantly increased to 83.33% with an average of 85.56 in Cycle II. Both teacher and student activities improved to the very good category. In conclusion, the implementation of Quizizz Paper Mode as a formative assessment media is effective in improving IPAS learning outcomes of fifth-grade students at MI Muhammadiyah Kalosi.